Sosialisasi Masyarakat Sadar Lingkungan di Kecamatan Pondokgede Kota Bekasi - Loen, Mishelei; Rosdiana, Rosdiana; Rahmawantari, Dhistianti Mei; Reztrianti, Diajeng; Puspitaningtyas, Ayu; Gustinya, Diana; Rejeki, Dewi; Utomo, Fajar Cahyo; Maulana, M. Kausar; Paramitra, Yuaniko; Safrianto, Arief Syaf; Herbayu, Tatag; Syahputra, Arry Dwi; Subagja, Iwan kurniawan; Saleh, Nino Nopriandi; Assegaf, Arief Rachmawan; Harri, Muhammad; Guswandi, Guswandi (Jurnal PKM Manajemen Bisnis, 2025)
Waste management is one of the greatest challenges faced by global communities today. Understanding the types, sources, and forms of waste is essential to raise awareness. This study aims to increase awareness and promote positive behavior in household waste management, focusing on the Environmentally Aware Community (MasDarLing) in Pondokgede District, which consists of 5 sub-districts and 78 neighborhood units (RW), through the UNKRIS Community Service Program (KKN). This research employs a qualitative analysis method with several stages, including preparation, implementation, and evaluation. The results show that 67% of the community understands the importance of not littering, 84% are aware of the need to sort waste before disposal, and 97% are conscious of the negative impacts of waste on the environment. Additionally, 84% of the community deposits inorganic waste at waste banks, and 97% have knowledge about composting and biopore absorption holes. The positive impacts of this activity include a cleaner environment, increased environmental awareness, and the establishment of more waste banks in Pondokgede District.